Delayed rather than early exercise training attenuates ventricular remodeling after myocardial infarction - Batista, Diego F. [UNESP] (2013)
UNESP Univ Estadual Paulista, Botucatu Med Sch, Dept Internal Med, Botucatu, SP, Brazil